Characterizing the histopathology of natural co-infection with Marek's disease virus and subgroup J avian leucosis virus in egg-laying hens. Issue 1 (2nd January 2018) - Wen, Yawen; Huang, Qi; Yang, Chengcheng; Pan, Ling; Wang, Guijun; Qi, Kezong; Liu, Hongmei
ABSTRACT: Marek's disease virus (MDV) and avian leucosis virus (ALV) are known to cause tumours in egg-laying hens. Here, we investigated the aetiology of tumours in a flock of egg-laying hens vaccinated against MDV. We carried out gross pathology and histopathological examinations of the diseased tissues, identified virus antigen and sequenced viral oncogenes to elucidate the cause of death in 21–22-week-old hens. At necropsy, diseased hens had distinctly swollen livers, spleens, and proventriculus, and white tumour nodules in the liver. The spleen and liver had been infiltrated by lymphoid tumour cells, while the proventriculus had been infiltrated by both lymphoid tumour cells and myeloblastic cells. Subtype J ALV (ALV-J) and MDV were widely distributed in the proventricular gland cells, and the lymphoid tumour cells in the liver and the spleen. In addition, positive ALV-J signals were also observed in parts of the reticular cells in the spleen. MDV and ALV-J antigens were observed in the same foci of the proventricular gland cells; however, the two antigens were not observed in the same foci from the spleen and liver. The amino acid sequence of the AN-1 (the representative liver tumour tissue that was positive for both ALV-J and MDV) Meq protein was highly similar to the very virulent MDV QD2014 from China. Compared to the ALV-J HPRS-103 reference strain, 10 amino acids (224-CTTEWNYYAY-233) were deleted from the gp85 protein of AN-1. We concluded that concurrent infection with MDV and ALV-J contributed to the tumorigenicity observed in the flock.